Strange Non-Chaotic Attractors with Unpredictable Trajectories - Akhmet, Marat; Fen, Mehmet Onur; Tola, Astrit (Journal of Vibration Testing and System Dynamics, 2026)
Continuous and discrete time systems possessing strange non-chaotic attractors are under investigation. It is demonstrated that unpredictable trajectories exist in the dynamics. A recent numerical technique, the sequential test, is utilized to show the presence of unpredictability.